An Analysis of the Fixabilities and Restrictions of Foreign Investments Policies and their Impact on the Investment Climate: The Case of The Russian Federation - Akmyrat KAKYSHEV; Vitaly Valerievich KOVALEV (Communications of International Proceedings, 2023)
The investment climate of a state or its region plays a key role in the investment decision in the eyes of a foreign investor. The investment climate of the Russian Federation is considered favorable and very promising by foreign investors, despite all the difficulties that have befallen it. Stimulating investment activity of the regions and improving the investment climate is a priority task at the political level. Over the past 30 years, the Russian government has implemented the process of attracting foreign investment into the domestic economic sector through the implementation and elaboration of legislative mechanisms. The other side of the coin is the mandatory consideration of private and public, foreign and domestic interests. In most cases, the interests of government and business do not coincide. Thus, in the Russian Federation we can observe two opposite, opposing tendencies. On the one hand, Russia longs for a large inflow of foreign investment and, in this context, is developing a legal regulatory mechanism that directs policy toward supporting the interests of investors. On the other hand, Russia wants to protect its national state interests by restricting, shackling and prohibiting the activities of foreign investors. All this requires a more comprehensive scientific study, both from a legal, juridical and economic point of view. The optimal combination of these two elements, the interests of the parties, will be the key to achieving a balance that will certainly lead to an improvement of the investment climate in Russia.
Keywords: Investment Attractiveness; Investment Climate; Legal Regulation; Foreign Investor.